Fenton-Based Electrochemical Degradation of Metolachlor in Aqueous Solution by Means of Bdd and Pt Electrodes: Influencing Factors and Reaction Pathways - Salazar-Gonzalez, R (Springer Verlag, 2019)
This work explores the role of electrode material and the oxidation ability of electrochemical advanced oxidation processes (EAOPs), such as electro-oxidation (EO) with or without H 2 O 2 production, electro-Fenton (EF), and UVA photoelectron-Fenton (PEF), in the degradation of metolachlor. The performance of the EAOPs using Boron-doped diamond (BDD) or Pt as anode has been compared from the analysis of decay kinetics, mineralization profile, and energy consumption using small undivided batch cell. Metolachlor concentration always decays following a pseudo-first-order kinetics. Using the Pt anode, none of the processes reaches 30% mineralization, including PEF. In contrast, the BDD anode showed a higher mineralization rate allowing almost total mineralization in PEF due to the synergetic action of UVA light and oxidant hydroxyl radicals formed in the bulk from Fenton’s reaction, as well as in the BDD, which has large reactivity to oxidize the pollutants. The increase in current density and decrease in metolachlor concentration accelerated the mineralization in PEF, although lower current efficiency and higher energy consumption was obtained. The GC-MS and HPLC analysis allowed the identification of up to 17 aromatics intermediates and 7 short-chain carboxylic acids. Finally, a reaction pathway for metolachlor mineralization by EAOPs is proposed. PEF with BDD allowed total removal of the herbicide in real water matrix and a high mineralization (83.82%). © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.